Dinámica poblacional de la Eisenia foetida alimentada con compostaje de residuos orgánicos, Quevedo 2022 - Guerrón Vera, Nury Yadira (2022)
The study aimed to determine the population dynamics of Eisenia foetida fed with organic waste composting. Four established treatments were used with semi-degraded organic matter (presence of mycelia), recycled cardboard from egg trays, bovine manure, waste from the agricultural sector (banana peels) and market waste (potatoes, carrots, corn leaves). The effect of organic waste compost on the productive parameters, reproductive parameters, and morphology of E. foetida was evaluated. Statistical analysis was performed with InfoStat, and Tukey's multiple range test to determine the difference between means. The effect of the compost of organic waste based on bovine manure